Pengaruh Citra Destinasi dan Pemasaran Digital Terhadap Keputusan Berkunjung Melalui Kepuasan Pengunjung Pada Monumen Nasional DKI Jakarta - Heny Ratnaningtyas; Nurbaeti Nurbaeti; Myrza Rahmanita (Tourism Scientific Journal, 2023)
This study aims to determine the influence of destination image and digital marketing on the decision to visit through visitor satisfaction at the National Monument. This type of research is quantitative descriptive using path analysis method. The population in this study is all visitors who come to Monas, while the sample consisted of 100 respondents using accidental sampling technique. The results showed that: (1) Destination image and digital marketing have a significant influence on visitor satisfaction; (2) Destination image and digital marketing partially have a significant influence on the decision to visit through visitor satisfaction. Based on the R-Square results, it shows that 41.2% of visitor satisfaction variable is influenced by destination image and digital marketing. Then 57.7% of the decision to visit variable is influenced by visitor satisfaction.The positive image of Monas affects satisfaction and the decision to visit because Monas strengthens the positive image of Jakarta city as an attractive tourist destination and has symbolic, historical, beauty, complete facilities, and high popularity values. Digital marketing at Monas influences visitor satisfaction and the decision to visit because it helps visitors find and plan visits through complete information and online ticket reservations and interactive experiences such as virtual tours. Visitor satisfaction has a significant influence on the decision to visit Monas because it can influence visitor recommendations and decisions to return to the destination in the future, which impacts the level of visits.